2007
DOI: 10.1111/j.1464-410x.2007.06860.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of attenuated neuronal nitric‐oxide synthase protein expression and accelerated arginase activity in impairing neurogenic relaxation of corpus cavernosum in aged rabbits

Abstract: RESULTSThe neurogenic relaxation and cGMP production in response to electrical-field stimulation were significantly impaired in aged cavernosal specimens. Western blot analysis showed that nNOS protein was highly expressed in cavernosal specimens from young rabbits, but was undetectable or greatly decreased in old rabbits, with no change in overall NOS activity. Arginase activity in aged cavernosal specimens was significantly higher than in young rabbits. Supplementing with excess L -arginine, or giving S-(2-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Consistently, it is known that NO synthase activity undergoes reduction with increasing age (Valdez et al 2004;Numao et al 2007). Interestingly, NO synthase also occurs in the inner mitochondrial membrane, functioning as a regulatory factor of respiration (Kato and Giulivi 2006), and reduced mitochondrial inner membrane as well as decreased expression of some respiratory enzymes have been found in GM-fed mice.…”
Section: Discussionmentioning
confidence: 87%
“…Consistently, it is known that NO synthase activity undergoes reduction with increasing age (Valdez et al 2004;Numao et al 2007). Interestingly, NO synthase also occurs in the inner mitochondrial membrane, functioning as a regulatory factor of respiration (Kato and Giulivi 2006), and reduced mitochondrial inner membrane as well as decreased expression of some respiratory enzymes have been found in GM-fed mice.…”
Section: Discussionmentioning
confidence: 87%
“…Other contributing factors could be the presence of endogenous NOS inhibitors (e.g., asymmetric dimethylarginine) and an up-regulation of arginase activity. High levels of asymmetric dimethylarginine have been demonstrated in multiple disorders in which NOS dysfunction has been implicated, including several of the disorders mentioned in the sections that follow, and increased arginase activity has been demonstrated in CC tissue in, for example, diabetes, aging, and smoking (Bivalacqua et al, 2001b;Imamura et al, 2007;Numao et al, 2007).…”
Section: A Risk Factors and Conditions Associated With Erectile Dysfmentioning
confidence: 99%
“…It has been reported that the enhanced arginase activity decreases L-arginine availability to NOS, thus impairing NO production (17). Enhanced arginase activity has been implicated in a number of conditions characterized by vascular dysfunction including pulmonary hypertension (18), intimal hyperplasia (19), agingassociated vascular dysfunction (20,21), and smokingrelated vascular dysfunction (22).…”
Section: Introductionmentioning
confidence: 99%